Perancangan Smart Trolley dengan Fitur Penghitung Barang Menggunakan Sensor E18-D80nk Berbasis Arduino Uno - M Naufal Mubarak Lubis; Hafni; Muhammad Zen (CV. Hawari, 2026)
The rapid development of the retail industry requires technological innovation to improve efficiency and enhance customer convenience during shopping activities. One common issue in supermarkets is that customers often forget the number of items placed in their shopping carts, leading to time inefficiency and potential disruption of shopping flow. This study aims to design and develop a Smart Trolley system based on Arduino Uno using the E18-D80NK distance sensor to automatically count the number of items. The system operates by detecting objects through infrared signals, processing the data via a microcontroller, and displaying the item count in real time on a 16x2 LCD screen. The device is equipped with additional features, including a stop-count button, item subtraction button, and reset function to enhance operational flexibility. Testing results indicate that the system is capable of accurately counting items and operates under stable voltage conditions according to component specifications. The proposed Smart Trolley is expected to assist customers in monitoring their shopping items accurately, improve time efficiency, and serve as an initial step toward simple technological implementation in the digital transformation of the retail sector.